End-stage renal disease risk in live kidney donors: what have we learned from two recent studies? - Lam, Ngan N. (Lippincott Williams & Wilkins, 2014)
PURPOSE OF REVIEW: Living kidney donation improves the lives of those with kidney failure, but there are potential risks to the donor. We review two recent publications that describe the long-term risk of end-stage renal disease (ESRD) in living kidney donors. RECENT FINDINGS: One study reported that the long-term risk (median follow-up 15.1 years) of ESRD was, in relative terms, 11-fold higher in living kidney donors compared to healthy nondonors, and suggested a hereditary association since all affected donors were biologically related to their recipients and the causes were predominantly immunological diseases. In a second study, we estimated that the long-term risk (median follow-up 7.6 years) of ESRD was, in relative terms, eight-fold higher in living kidney donors compared to healthy matched nondonors. In both studies, the absolute increase in the 15-year incidence of ESRD from donation was below 0.5%. There are limitations in these studies, which have raised questions about the accuracy of the estimates of risk. SUMMARY: The results of these studies should be discussed with potential living kidney donors with an emphasis on the low 15-year incidence of ESRD following donation. The lifetime incidence of ESRD for donors of different age, race, and other characteristics requires further study.